Analisis Faktor Penyebab Kerusakan Berkas Rekam Medis di Puskesmas Nogosari Kabupaten Jember - Selvia Juwita Swari; Sakinah Salsabila; Maya Weka Santi; Angga Rahagiyanto; Gamasiano Alfiansyah (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2024)
Medical records at The X Community Health Center are easily torn due to overfilled filing racks, making it difficult to retrieve medical record files. Forcing the files out can result in torn records. Approximately 7.35% of medical records were found to be damaged. The aim of this study was to analyze the factors causing damage to medical records based on the 7M aspects. The research was qualitative, with data collected through interviews, observations, and documentation. The research subjects consisted of 1 registration officer, 1 filing officer, 1 administrative staff member, 1 head of administration, and the Head of the X Community Health Center. Data were analyzed through data reduction, data presentation, and conclusion drawing. The results showed that the damage to medical records was caused by several factors, including man (education level, lack of knowledge, and no training), machines (insufficient number of medical record storage racks), methods (no SOP for medical record maintenance), materials (medical record folder materials), media (physical environment), motivation (no rewards or punishments), and money (insufficient budget for procuring medical record folders). It is recommended that The X community health center provide medical record maintenance training and develop and implement SOP for medical record maintenance.